Fridtjof Nansen som forfatter : en litterær vurdering av reiseskildringene - Wærp, Henning Howlid (University of Tromsø, 2012)
The article gives an evalutation of Fridtjof Nansen´s travelogues and expedition reports from a literary perspective, focusing on Gennem Sibirien (1914).